1998
DOI: 10.1520/jfs16084j
|View full text |Cite
|
Sign up to set email alerts
|

Drug Concentration in Selected Skeletal Muscles

Abstract: We evaluated the homogeneity of drug concentrations in muscle in 14 cadavers, comprising 11 drug overdoses and three cases of chronic therapeutic drug use. Analyses were performed on samples from twelve named muscles and femoral venous blood. Standard analytical techniques and instrumentation were used throughout. There was marked within-case variability in drug concentrations with highest:lowest concentrations ranging up to 21.7. Overall highest concentrations were found in the diaphragm and mean diaphragm:bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Therefore, iliopsoas muscle can be an interesting specimen when the usual samples for drug assay are lacking. However, muscle sampling is not recommended for some other substances (such as temazepam, prothiaden, paracetamol and amitriptyline) [16,17]. These studies did not include concentrations in iliopsoas muscle, however.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, iliopsoas muscle can be an interesting specimen when the usual samples for drug assay are lacking. However, muscle sampling is not recommended for some other substances (such as temazepam, prothiaden, paracetamol and amitriptyline) [16,17]. These studies did not include concentrations in iliopsoas muscle, however.…”
Section: Discussionmentioning
confidence: 99%
“…Due to faster putrefaction of internal organs, muscle tissue is longer available for analysis than internal organs. However, the interpretation of drug concentrations is difficult due to postmortem distribution and degradation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported that drug level in skeletal muscle reflects that in blood [3][4][5], but others suggested that skeletal muscle is suitable only for qualitative analysis [6,7]. To our knowledge, there is little literature about tissue distributions of nicotine and cotinine in human autopsy cases of smokers.…”
Section: Discussionmentioning
confidence: 99%